“Seek Knowledge from the Cradle to the Grave”: Islamic Educational Philosophy as a Driver for Community-Based Early Childhood Education - Taufiki, Riki; Haekal, Muhammad (Seulanga : Jurnal Pendidikan Anak, 2025)
Despite growing recognition of early childhood education’s (ECE) importance, rural communities in post-conflict settings often lack access to quality ECE services. This study examines how Islamic educational philosophy inspired and sustained a community-driven ECE initiative in rural North Aceh, Indonesia, following decades of conflict and natural disaster. This research investigated the sources of inspiration that motivated a rural Muslim community to establish and operate a community-based early childhood education centre, with particular focus on how religious values catalysed collective action for educational development. An ethnographic case study approach was employed in Gampong Blang, North Aceh, involving observations, interviews, and document analysis with 27 participants including community members, village stakeholders, and educators. Data were analysed through Al-Attas’ concepts of ta’dib (ethical education) and adab (proper conduct reflecting social consciousness). The Islamic principle “seek knowledge from the cradle to the grave” served as a powerful catalyst for community mobilisation, inspiring villagers to transform their traditional meunasah (Islamic community centre) into a modern ECE facility. Al-Attas’ educational philosophy, emphasising the balance between ilmu (knowledge) and adab (moral character), resonated with local aspirations for holistic child development. The community successfully integrated religious values with contemporary educational practices, creating culturally responsive pedagogy that honoured both Islamic teachings and local traditions. This study demonstrates how religious educational philosophy can effectively motivate grassroots educational initiatives in Muslim communities. The findings suggest that ECE development in Islamic contexts benefits from approaches that integrate spiritual and academic learning, challenging purely secular early childhood education models. The research offers insights for developing culturally responsive ECE programs that respect local values while meeting contemporary educational standards.